Kajian Komprehensif terhadap Persamaan dan Perbedaan Ketentuan Tindak Pidana Penggelapan dalam KUHP Lama 1946 dan KUHP Baru 2023 - Thessa Lonians Marghareta Tentua; Divanny Elisabeth Oktavia Panjaitan; Irma Dwiyanti; Taun Taun (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The development of society and the increasing complexity of legal relations necessitate the reform of the national criminal law system. This research is motivated by the need to examine the relevance and responsiveness of provisions governing the criminal act of embezzlement in the 1946 Indonesian Criminal Code (Old KUHP) and the 2023 Indonesian Criminal Code (New KUHP). The aim of this study is to analyze the substantive similarities and differences between the two codifications of criminal law, and to assess the extent to which the New KUHP addresses the challenges of modern legal systems. This study employs a normative juridical method using a comparative approach to relevant legislation. The findings reveal that, while both codes share fundamental elements of embezzlement and similar sentencing structures, the 2023 KUHP adopts a more progressive approach. Key reforms include the expansion of legal subjects to include corporations, the adjustment of value thresholds for minor embezzlement, the implementation of more flexible sanctions such as fines, and the strengthening of restorative justice principles. The implications of these findings indicate that the 2023 KUHP is more adaptive to socio-economic dynamics and the needs of a modern criminal justice system. Accordingly, the New KUHP offers a more relevant and contextual legal framework, particularly in addressing embezzlement offenses.